Polscy liberałowie gospodarczy wobec polityki ekonomicznej rządu w latach 1935–1939. Wybór problematyki - Chłopecki, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
It is worth emphasizing that neither Adam Krzyżanowski nor Ferdynand Zweig or Edward Taylor belonged to the ruling camp, nor did they identify with it politically. Their ideas and proposals, however, did not go “unnoticed” by Minister Eugeniusz Kwiatkowski who was at that time responsible for the Polish economy. Economic policy after Józef Piłsudski’s death was not conducted in a uniform manner, which largely resulted in inability to make changes, including those requested by the liberals. On the one hand Polish economy sought to balance its expenditure and revenue and strengthen its position after a period of great crisis — a policy led by Eugeniusz Kwiatkowski, on the other — the the opinion of the military circles was that the Polish economy should be more focused on military and heavy industry. In this issue, however, there was also a lack of common solutions and a number of disputes occured between the castle group, whose representative was Kwiatkowski, and military circles.
Keywords: II Rzeczpospolita; cykl koniunkturalny; obóz rządzący; reforma; koncepcje; polityka gospodarcza